2018
DOI: 10.1016/j.aller.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Single and multiple food allergies in infants with proctocolitis

Abstract: There is no difference in clinical presentations between infants with single and multiple food allergies. However, infants with multiple food allergies have a high blood total eosinophil count and are more likely to have a positive skin prick test and/or positive specific IgE results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
1
14
0
7
Order By: Relevance
“…We found the frequency of multiple food allergies to be 24.1%; egg, nuts, and meat were the most common accompanying culprit foods in our group. In accordance with our results, Koksal et al (20) observed that most of the patients who developed tolerance after 2 years of age had multiple food allergies.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found the frequency of multiple food allergies to be 24.1%; egg, nuts, and meat were the most common accompanying culprit foods in our group. In accordance with our results, Koksal et al (20) observed that most of the patients who developed tolerance after 2 years of age had multiple food allergies.…”
Section: Discussionsupporting
confidence: 94%
“…Hence, physicians should take into account dietary habits in their geographic region when eliminating foods, particularly, in patients who do not respond to removal of cow's milk. Lucarelli et al (19) reported multiple food allergies as 5%, whereas this rate was as high as 34% in another study by Koksal et al (20). We found the frequency of multiple food allergies to be 24.1%; egg, nuts, and meat were the most common accompanying culprit foods in our group.…”
Section: Discussionmentioning
confidence: 94%
“…The most common triggering foods in both groups of infants in our study, and with no difference between groups, were cow’s milk and egg. Koksal and colleagues found that infants with FPIAP developed tolerance to egg later than those achieving tolerance to milk [ 34 ]. Avoidance of dairy foods in the mothers’ diet did not influence the acquisition of overall tolerance, while the elimination of more foods appears to be associated with a later development of tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…FPIES was associated with eosinophilic inflammation in histology of colonic biopsy in some cases (14). Infants with multiple food allergies have a high blood total eosinophil count (15). It is known that eosinophils can release cytokines and chemokines, that modulate inflammatory responses and may also affect tissue remodelling and fibrosis by releasing transforming growth factors (16).…”
Section: Discussionmentioning
confidence: 99%